Ethnocentric Hate Speech as an Impediment to National Development in Nigeria: Implications for Peaceful Communication - Onoja, Peter; Gbeyonron, Clifford Irikefe (Indonesian Journal of English Language Studies (IJELS), 2025)
Nigeria is a heterolingual, multi-religious, multi-ethnic, and multicultural country. The constitution of the country allows freedom of expression. Despite having English as a lingua franca, Nigerians use their respective indigenous languages. The inability of the citizens to manage this diversity has led to the use of ethnocentric hate speech by members of different linguistic groups against one another. This is inimical to national development. This intervention aimed to establish the effect of ethnocentric hate speech on national development in Nigeria and how applied peace linguists can serve as advocates of peaceful communication. Applied peace linguistics plays the role of facilitating dialogue and conflict resolution in Nigeria. It assists in ensuring peaceful communication and counter speech. Thus, ensuring early warming on speeches that can escalate violence. A questionnaire was administered to 900 respondents in the townships from January to July 2024. The researchers also conducted focus group discussion sessions with 19 groups of eight (8) participants in 19 townships in Nigeria. The major finding of the study indicates that an overwhelming majority of the respondents detest ethnocentric hate speech. They agree that ethnocentric hate speech engenders suspicions and phantom tolerance in society, thus an impediment to national development. Phantom tolerance is characterised by the pretence that one is tolerating another while, in reality, one hates the other. This study concludes that peaceful communication should be encouraged in the school curriculum and made a norm for general interaction in the country to build trust and foster national development.